Nematophagous fungi and their influences on parasitic control in sheep (Research, Society and Development, 2023)
Infections caused by gastrointestinal nematodes in sheep have become a recurring problem due to the difficulty of eradicating these parasites from the environment. The use of alternative methods, such as biological control, using nematophagous fungi, is a suitable tool for producers. The objective of this review is to provide information, disseminate knowledge, and clarify doubts. Nematophagous fungi are microorganisms adapted to survive in the soil of various cultures, feeding on present, infectious, or free-living larvae, which can also be harmful. In this work, the groups and genera of interest in the context of nematodes were compiled, dividing them according to the mode of action. It is important to note that, under appropriate circumstances, the functioning of the nematophagous fungi may be impaired, even in the presence of proven larvae. Despite the numerous applications for the use of these microorganisms, the work points out some aspects, such as temperature and humidity, as determining factors. The described study concludes the different types and genera of fungi, modes of action, predation, colonization, and habits, facilitating understanding. Some difficulties need to be overcome, such as climatic variations, lack of prey, and their misuse, which it is up to the interested researcher to manipulate.